Insolvensi Dan Likuiditas Pada Kinerja Keuangan Bank Syariah - Aminar Sutra Dewi; Yessy Sentya Gunawan (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to examine the extent to which insolvency and liquidity ratios affect financial performance. This research is a quantitative research method using data in the form of financial statements of the Islamic banking sector at the Financial Services Authority for the period 2017 – 2021. This study used a purposive sampling method as a sampling technique. The variables used in this study are insolvency (X1), liquidity (X2). Based on the analysis that has been carried out, it can be concluded from this research that: Insolvency has a significant positive effect on the financial performance of Islamic banking companies registered with the financial services authority in 2017-2021. This means that the companies listed in the OJK do not experience bankruptcy. Likewise with the Liquidity ratio which has a positive and significant effect on the financial performance of Islamic banking companies registered with the financial services authority in 2017-2021. This means that Islamic banking companies are able to fulfill their short-term obligations at maturity. Therefore, the financial performance of Islamic banking in Indonesia is good and growing. In this study, the data analysis method used was descriptive statisrics using the stata 14 program.